Effects of heat treatment on the microstructure and properties of cold-forged CoNiFe medium entropy alloy. (July 2019) - An, X.L.; Zhao, H.; Dai, T.; Yu, H.G.; Huang, Z.H.; Guo, C.; Chu, Paul K.; Chu, C.L.
Abstract: The effects of heat treatment on the microstructure and properties of cold-forged two-dimensional (2D) CoNiFe medium entropy alloy (MEA) are determined. Compared to the as-cast specimen with a columnar crystal structure, the cold-forged CoNiFe MEA has a heavily fragmented microstructure with deformation twins. As the annealing temperature is increased, the grain size becomes larger markedly. Annealing at 900 °C yields a fully recrystallized microstructure with a large population of annealing twins and the new orientation exhibits a first-order twin relationship (60° <111> rotation) during recrystallization. Moreover, the CoNiFe HEA annealed at 900 °C possesses excellent ductility (ε = 50%) and work-hardening ability (σUTS -σY  = 246 MPa, σUTS /σY  = 0.5), which depend on the annealing twins, dislocations, as well as micro-shear bands in the grains. Analysis of the fracture surface indicates that the main failure mechanism is ductile. Meanwhile, no phase separation occurs as the temperature is raised from 0 °C to 1000 °C as shown by the expansion rate versus temperature relationship, indicating that the materials have good stability at high temperature. The thermal expansion coefficient (CTE) of the sample annealed at 1100 °C for 1 h is 12.1 × 10 −6  K −1 which is less than that of traditional metals (14.4–16 × 10 −6  K −1 ). Highlights: Effect of two-dimensional (2D) and annealing treatments on the microstructures and properties of CoNiFe MEA are investigated. The cold forged CoNiFe MEAs shows a heavily fragmented microstructure with deformation twins. anThe forged CoNiFe HEA annealed at 900 °C show a excellent ductility and work-hardening ability. The forged CoNiFe MEAs possess stability in high temperature according to thermal expansion coefficient rate curves.